Turbulence Sets the Initial Conditions for Star Formation in High-Pressure Environments - Rathborne, J.; Longmore, S.; Jackson, J.; Kruijssen, J.; Alves, J.; Bally, J.; Bastian, N.; Contreras, Y.; Foster, J.; Garay, G.; Testi, L.; Walsh, Andrew (Institute of Physics Publishing, 2014)
Despite the simplicity of theoretical models of supersonically turbulent, isothermal media, their predictions successfully match the observed gas structure and star formation activity within low-pressure (P/k < 10 5 K cm-3) molecular clouds in the solar neighborhood. However, it is unknown whether or not these theories extend to clouds in high-pressure (P/k > 10 7 K cm-3) environments, like those in the Galaxy's inner 200 pc central molecular zone (CMZ) and in the early universe. Here, we present Atacama Large Millimeter/submillimeter Array 3 mm dust continuum emission within a cloud, G0.253+0.016, which is immersed in the high-pressure environment of the CMZ. While the log-normal shape and dispersion of its column density probability distribution function (PDF) are strikingly similar to those of solar neighborhood clouds, there is one important quantitative difference: its mean column density is one to two orders of magnitude higher. Both the similarity and difference in the PDF compared to those derived from solar neighborhood clouds match predictions of turbulent cloud models given the high-pressure environment of the CMZ. The PDF shows a small deviation from log-normal at high column densities confirming the youth of G0.253+0.016. Its lack of star formation is consistent with the theoretically predicted, environmentally dependent volume density threshold for star formation which is orders of magnitude higher than that derived for solar neighborhood clouds. Our results provide the first empirical evidence that the current theoretical understanding of molecular cloud structure derived from the solar neighborhood also holds in high-pressure environments. We therefore suggest that these theories may be applicable to understand star formation in the early universe.